Evaluating aesthetics for user-sketched layouts of symmetric graphs. (October 2018) - Lin, Chun-Cheng; Huang, Weidong; Liu, Wan-Yu; Chen, Wen-Lin
Abstract: In evaluating aesthetics of graph drawings, recent works have provided participants with an adjacency list of a graph and asked them to sketch a pleasing layout of the graph. However, this line of research has not considered aesthetics for user-sketched layouts of graphs with symmetries, which are an important property of a given graph drawing. Therefore, the work reported in this paper focuses on empirically evaluating aesthetics for user-sketched layouts of symmetric graphs. We provided participants adjacency lists of two symmetric graphs and asked them to sketch the two graphs. We analyzed whether symmetries were shown in user-sketched drawings, and further analyzed the aesthetics based on their drawing processes and drawing preferences. In addition, our experiment includes multiple stages to analyze whether the participants had the potential learning ability to draw symmetric structures of graphs. We found that in drawing symmetrical graphs, showing symmetry was likely considered more important than minimizing edge crossings, and that most participants made substantial progress in their ability to create symmetric drawings after going through the experimental stages.